CircSLC7A2 protects against osteoarthritis through inhibition of the miR‐4498/TIMP3 axis. (7th May 2021) - Ni, Weiyu; Jiang, Chao; Wu, Yizheng; Zhang, Haitao; Wang, Lili; Yik, Jasper H.N.; Haudenschild, Dominik R.; Fan, Shunwu; Shen, Shuying; Hu, Ziang
Abstract: Objectives: Circular RNAs (circRNAs) are noncoding RNAs that compete against other endogenous RNA species, such as microRNAs, and have been implicated in many diseases. In this study, we investigated the role of a new circRNA (circSLC7A2) in osteoarthritis (OA). Materials and Methods: The relative expression of circSLC7A2 was significantly lower in OA tissues than it was in matched controls, as shown by real‐time quantitative polymerase chain reaction (RT‐qPCR). Western blotting, RT‐qPCR and immunofluorescence experiments were employed to evaluate the roles of circSLC7A2, miR‐4498 and TIMP3. The in vivo role and mechanism of circSLC7A2 were also conformed in a mouse model. Results: circSLC7A2 was decreased in OA model and the circularization of circSLC7A2 was regulated by FUS. Loss of circSLC7A2 reduced the sponge of miR‐4498 and further inhibited the expression of TIMP3, subsequently leading to an inflammatory response. We further determined that miR‐4498 inhibitor reversed circSLC7A2‐knockdown‐induced OA phenotypes. Intra‐articular injection of circSLC7A2 alleviated in vivo OA progression in a mouse model of anterior cruciate ligament transection (ACLT). Conclusions: The circSLC7A2/miR‐4498/TIMP3 axis of chondrocytes catabolism and anabolism plays a critical role in OA development. Our results suggest that circSLC7A2 may serve as a new therapeutic target for osteoarthritis. Abstract : The expression of the novel circular RNA, circSLC7A2, is important for maintaining ECM homeostasis and protecting cartilage against OA progression. CircSLC7A2 is regulated by FUS and functions through miR‐4498/TIMP3 axis, which is effective and comprehensive in alleviating inflammation, inhibiting catabolic enzymes, introducing anabolic enzymes and preventing cell apoptosis that resulted in maintaining cartilage ECM, thus preventing or delaying OA progression.